Multiple Microwave Frequency Measurement With Improved Resolution Based on Stimulated Brillouin Scattering and Nonlinear Fitting - Wenting Jiao; Ke You; Junqiang Sun (IEEE Photonics Journal, 2019)
A multiple microwave frequency measurement is experimentally demonstrated by exploiting stimulated Brillouin scattering and nonlinear fitting. Through sweeping a reference frequency during the stimulated Brillouin scattering process, the frequency information of microwave signal to be measured is detected by the created mapping between the total output power of the system and the reference frequency. Nonlinear fitting is utilized to mitigate the limitation of Brillouin gain spectrum linewidth and the measurement resolution is improved significantly. The minimum distinguishable frequency interval of 18 MHz is realized with the proposed scheme, and the measurement error is less than 5 MHz with in a range of 21.42 GHz. This approach offers an effective way to implement the measurement on continuous microwave sinusoidal signal with a number of frequencies of about 1190 in photonics domain.